Discontinuation and restarting in patients on statin therapy: a cohort study using a primary care database - Vinogradova, Yana; Coupland, Carol; Brindle, Peter; Hippisley-Cox, Julia (BMJ Publishing Group, 2016)
Objectives: To estimate rates of discontinuation and restarting of statins, and to identify patient characteristics associated with either discontinuation or restarting.